Regulation of Fibrinogen Synthesis in Portal Hypertension - Grün, M; Liehr, H; Brunswig, D; Thiel, H (Thrombosis and Haemostasis, 1974)
The fibrinogen synthesis rate in patients with cirrhosis of the liver is enhanced. To confirm this, both experimental and clinical investigations were carried out. The fibrinogen synthesis rate was studied, using the incorporation rate of 14-C-Leucine into thrombin clottable plasma protein in the setting of experimental portal hypertension caused by gradual occlusion of the portal vein. Under these conditions the plasma distribution space increased to 148% of the control (day 6). This was dependent on the amount of the portocaval shunt volume. While plasma fibrinogen concentration remained unaltered, the plasma fibrinogen pool increased to 154% of the controls. At the same time, the fibrinogen synthesis rate increased to 159%. In relation to liver weight per 100 gm body weight the rate of synthesis was much more enhanced (211 % of control). During the decline to normal plasma volume, due to a decrease of portocaval shunt volume, the fibrinogen synthesis was inhibited (61% of control).Under clinical conditions in patients with cirrhosis and portal hypertension, the pathophysiological state is in important aspects comparable to the experimental model. A group of 28 patients with cirrhosis was investigated from the same point of view. In these patients the plasma volume and the plasma fibrinogen pool was markedly increased, depending again on the portocaval shunt volume but not on the portal pressure. From these data it is concluded that in patients with cirrhosis fibrinogen synthesis is enhanced.